Sex in our City - Ang, Hwee Min (2018)
This project is a feature exploring sex and related concepts. We interviewed people from sex-related industries, communities and businesses to find out how they function in supposedly conservative Singapore. These include: Sex workers, BDSM practitioners, swingers, people who sell or buy sex toys and more. We learned about growing communities, private parties and personal struggles. We also heard how these activities have changed the lives of participants and how these people found their place — be it on the Internet or in real life. This is a multimedia project. Please visit our website at sexinourcity.com (available until March 2019) or sexinourcityfyp.wixsite.com/project (after March 2019). Optimised for 13" screens, best viewed on Google Chrome.